PENGARUH INKLUSI KEUANGAN TERHADAP STABILITAS SISTEM KEUANGAN (STUDI KASUS : SELECTED ASIA DEVELOPING COUNTRIES TAHUN 2011-2016) - Hardiyanto, Yudha Prakasa (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2019)
This research aims to analyse the financial inclusion relationship to financial system stability in developing countries in Asia. The data used in this study are panel data, a combination of time series data from 2011-2016 and cross section of seven developing countries in Asia, namely Bangladesh, Indonesia, India, Malaysia, Pakistan, Thailand and Turkey. This research was conducted with quantitative methods. Quantitative method is done by tobit regression estimation technique The use of tobit regeresi estimation technique is used because the dependent variable is AFSI in a certain range or censored.The result of this study indicate that financial inclussion has a negative and insgignificant influence on financial system stability in selected Asia developing countries. In addition, other variables that a significant effect on financial system stability are the ratio of current assets to deposits and short-term funding, non foreign direct invesment and private credit ratio, significant influence on teh stability of the countryâ€™s financial system.Â